Efeitos da fotobiomodulação (660nm) isolada ou associada a dermocosmético a base de Urucum no fotoenvelhecimento: um estudo experimental controlado - Soares, Michelle Barbosa (Universidade Federal de São Carlos, 2020)
When exposed to long-term ultraviolet radiation (UVR), the skin may cause photoaging which, in its histological configuration, presents degradation of the extracellular matrix in the epidermis and dermis. glandular hyperplasia (TSOURELI-NIKITA et al., 2006; YAAR AND GILCHREST, 2007) and continuous production of reactive oxygen species in order to impair the balance between pro-oxidant production and antioxidant defense. The objective of this in vivo controlled double-blind experimental study was to evaluate the effects on oxidative stress of PBL using the LED device (660 nm), and an annatto extract-based dermocosmetic, applied as separate and associated therapies. in photoaged mice. Fifty 8-week-old male BALB / c mice weighing 25-30 grams from the Central Biotery of the Federal University of Viçosa-MG were used for the study. The animals were exposed to UVR over a period of 20 weeks. After photoaging induction, the animals were randomly allocated into 5 groups, each group consisting of 10 animals: 2 control groups and 3 treatment groups (LED group, Urucum group and LED + Ucurum group). The results showed that the treatment with the annatto dermocosmetic decreases the levels of MDA and NO2 / NO3, consequently there is also a decrease in SOD and CAT and an antioxidant effect. Treatment with Urucum-based dermocosmetics and / or LED provided histological and histomorphometric changes in the epithelial tissue of photoaged mice, such as increased dermal cellularity, increased Type I collagen, increased epidermis thickness, and decreased epidermal recesses. in some groups treated in this study. Thus, it was concluded that the dermocosmetic base of Urucum extract was able to reduce MDA and NO2 / NO3 suggesting a balance between the levels of antioxidants SOD and CAT in photoaged mice, producing hepatological and histomorphometric changes. The treatment with 660nm LED applied on creep of 21.25 J / cm2, application time of 1 min and 54 J / point showed no changes in oxidative stress and antioxidant levels in the epithelial tissue of photoaged mice. In future research the clinical application in humans of dermocosmetic becomes important to evaluate the effects on daily use and anti-aging effects.
Effects of photobiomodulation (660nm) isolated or associated with Urucum-based dermocosmetics in photoaging: a controlled experimental study
Keywords: Fotoenvelhecimento; LED; Urucum; Espécies reativas de oxigênio; Photoaging; Reactive oxygen species; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL